Water management in a novel proton exchange membrane fuel cell stack with moisture coil cooling - Xiao, Biao (2023)
Water flooding causes severe degradation of the performance and lifetime of proton exchange membrane fuel cell (PEMFC). In this study, a novel PEMFC stack with in-built moisture coil cooling was designed and the effects of moisture coil cooling on water management in the new PEMFC stack under various operating conditions were investigated. The result showed that the performance of the PEMFC stack was significantly improved due to the moisture condensation under high current density, high operating temperature, high relative humidity and high operating pressure. The output power was increases by 21.62% (525.71 W) at 1600·mA cm−2 while the increased parasitic power was no more than 35W. Moreover, degradation of the cathode catalyst layer after 100 h operation was also reduced by using moisture coil cooling. Compared with the situation without moisture condensation, the maximum decay rate of the cathode catalyst layer thickness after 100 h operation was reduced by 13.01%. Accordingly, the novel design is valuable and can be widely used in the future design of PEMFC.